Key knowledge and skills university students need in a digital environment - T. V. Salynskaya; A. A. Yasnitskaya (Управление)
The era of digital transformation implies fundamental changes in society, educational processes, professional activities and everyday life of people. This allows building economic relations in a new way, establishing cultural ties, planning, making and implementing decisions. Digital technologies are becoming an important tool for educational transformation and they affect the value of the digital system positively. The purpose of the article is to evaluate the introduction of digital technologies into the system of teaching students at the university. The empirical methods such as questioning, analysis, study and generalization are used in the research. The paper concludes that undergraduate students consider the active introduction of digital transformation into the educational process as a necessary component for acquiring modern digital competencies. The perspectives for the study lie in the introduction of modern digital technologies focused on the widespread use of active teaching methods that contribute to the deepening of the professional specialization of the educational process in the era of the digital economy. The scientific novelty of the paper bases on the fact that the authors examine the impact of digital technologies used in the process of teaching at a university on the degree of students’ readiness to enter a new educational space and to participate in the educational process based on the use of information, communication and digital technologies.